Application of Cleaner Technology concepts in the arm coil assembly process of hard disk drive manufacturing - Rungchat Chompu-Inwai (2018)
The objectives of this research are to improve raw material and energy consumption efficiency, as well as reduce defects and the use of chemicals in the arm coil assembly process of hard disk drive manufacturing in the case study company by applying the Cleaner Technology concepts. The four main sequential steps used in this research were: (1) pre-assessment, (2) assessment, (3) feasibility study, and (4) implementation. In the first step, raw data, such as process flows, raw material usage and defects data were collected. In the second step, the loss during production and causes of loss were analyzed. Opportunities to reduce raw material, chemical and energy wastage could then be recommended. The next step was to evaluate the feasibility and potential benefits of a particular Cleaner Technology opportunity. Finally, in the last step, after a thorough evaluation and implementation of the opportunities to apply clean technology, the results showed that Arm Coil defects could be reduced by improving the production process using the ECRS technique. ECRS stands for Eliminate, Combine, Rearrange and Simplify. This improvement reduced arm coil defect rates from 0.48% to 0.15%, thus saving approximately 139,638 Thai Baht per month. In addition, production stoppage decision made by workers was used to increase employee involvement in defect detection. Allowing workers to participate in such a decision was an effective way to reduce defect rate and could motivate workers to produce a better quality job. This resulted in arm coil defects reducing from 0.41% to 0.025%, with about 74,562 Thai Baht per month saving. Additionally, an increase in the efficiency of electricity consumption occurred, by increasing the speed of the infrared oven conveyor belt, improving average productivity from 533 pieces/hour to 560 pieces/hour, without adversely affecting product costs and quality, thus producing products of up to the value of 206,242 Thai Baht per month. Furthermore, the new 2-layer curing equipment was designed, developed and used. The upper layer of the equipment was used for arm curing and the lower layer was used for arm coil curing. The result of using such equipment led to a saving of approximately 25,502 Thai Baht per month in electricity costs, without affecting product quality. The outcome of these Cleaner Technology applications was that total costs of approximately 239,702 Thai Baht per month were able to be saved.